Peran Regulasi dalam Pengelolaan Sumber Daya Air pada Industri Pertambangan - Hilda Chaerunisa (Savana, 2024)
This article discusses the applicable regulations in water resource management in the mining industry and how they are implemented in the perspective of Pelalawan District Court Decision Number 350/Pid.B/LH/2019/PN.Plw, which aims to determine and assess the applicable regulations and arrangements in Indonesia. This research adopts normative legal analysis methods and case studies. Law Number 17 of 2019 concerning Water Resources states that water resource management must be carried out sustainably, including the use of water for business activities such as mining. One human activity that can reduce river water quality is sand mining, which can occur due to the discharge of washing waste into rivers. The main challenge in implementing mining law in Indonesia is that consistent enforcement of regulations can create uncertainty for industry players and trigger conflicts between the government, mining companies, and local communities. Emphasizes the importance of water resource management in the mining industry in Indonesia. The need for increased supervision of mining activities and more consistent law enforcement.